Quantitative analysis of impurities deposited on the Plasma-Facing Components of EAST tokamak using a portable LIBS device - Zhenhua Hu; Xue Bai; Huace Wu; Ran Hai; Fang Ding; Muhammad Imran; Cong Li; Hongbin Ding; Guang-Nan Luo (Nuclear Materials and Energy)
In this work, the characterization of impurities deposited on the Plasma-Facing Components (PFCs) of the EAST tokamak, — including the tungsten upper and lower divertors (UD, LD), the molybdenum first wall on the high-field side (HFS), and the graphite main guard limiter (ML) — is reported using a portable Laser-Induced Breakdown Spectroscopy (LIBS) device. The LIBS analysis revealed that the primary impurity elements deposited on the PFCs are Cu, W, Fe, Li, Mo, and Ca. Notably, significant amounts of Cu, W, Fe, Li, and Mo impurities were observed on the ML surface. On both the upper and lower divertors (UD, LD) surfaces, trace amounts of Cu and Fe impurities were detected. The results on HFS showed a low level of Cu, W, and Fe impurities on its surface. Additionally, the Calibration-Free LIBS (CF-LIBS) method was implemented to determine the relative content of impurities on the PFCs. The quantitative results of the deposited impurities on PFCs further provide a more detailed interpretation of the variations in impurity deposition. The successful in situ assessment of impurities deposited on the EAST tokamak using a portable LIBS device demonstrates the potential for integrating the LIBS system into a remote handling system. These results offer valuable insights into the dynamics of impurities in controlled fusion devices, which can contribute to enhancing impurity control methods and improving device performance.